2006
DOI: 10.1248/bpb.29.1319
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Selective Cyclooxygenase (COX)-1 and COX-2 Inhibitors on Anorexic Response and Prostaglandin Generation in Various Tissues Induced by Zymosan

Abstract: We have shown that anorexic response is induced by intraperitoneal injection of zymosan in mice, although the role of prostaglandins in this response is relatively unknown as compared with lipopolysaccharide (LPS)-induced anorexic response. Indomethacin (0.5 and 2.0 mg/kg), a non-selective cyclooxygenase (COX) inhibitor, as well as meloxicam (0.5 mg/kg), a selective COX-2 inhibitor, but not FR122047 (2.0 mg/kg), a selective COX-1 inhibitor, attenuated zymosan-induced anorexia. Zymosan injection elevated COX-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Recently, we found that central CRTH2 but not DP1 regulates emotional aspects of lipopolysaccharide (LPS)-and tumor-induced sickness behaviors [16]. Given that LPS-induced sickness behavior critically involves the COX-2-PG pathway [17][18][19][20][21], PGD 2 -CRTH2 is likely to modulate sickness behavior by regulating COX-2-mediated signaling in the brain [16]. Furthermore, several lines of evidence suggest that sickness behavior and depression share many of the same symptoms and common inflammatory pathways [22].…”
Section: Q2mentioning
confidence: 99%
“…Recently, we found that central CRTH2 but not DP1 regulates emotional aspects of lipopolysaccharide (LPS)-and tumor-induced sickness behaviors [16]. Given that LPS-induced sickness behavior critically involves the COX-2-PG pathway [17][18][19][20][21], PGD 2 -CRTH2 is likely to modulate sickness behavior by regulating COX-2-mediated signaling in the brain [16]. Furthermore, several lines of evidence suggest that sickness behavior and depression share many of the same symptoms and common inflammatory pathways [22].…”
Section: Q2mentioning
confidence: 99%
“…25) In addition, an increase in prostaglandin synthesis through inflammation-induced COX-2 in the CNS is also implicated in sickness behavior. 13,22,26,27) We previously reported that genipin, a main constituent of Gardeniae Fructus, is one of the component herbs of KKT, ameliorated LPS-induced sickness behavior and inflammation in the hypothalamus and amygdala 2 h after LPS administration. 15) Therefore, it seemed likely that KKT would also attenuate LPS-induced inflammation in the hypothalamus and amygdala 2 h after LPS administration.…”
Section: Discussionmentioning
confidence: 99%
“…For the determination of PGE 2 content, ethanol extracts from the small intestine prepared as described above were dried under nitrogen gas. PGE 2 content in the samples was determined using enzyme immunoassay kits (Cayman Chemicals, Ann Arbor, MI) [21]. …”
Section: Methodsmentioning
confidence: 99%
“…The specimens were blotted onto dry filter papers to remove excess water. The expression levels of COX-1 and COX-2 in the small intestine were determined by western blot analysis as described previously [21]. …”
Section: Methodsmentioning
confidence: 99%